NONBIOLOGICAL FRACTIONATION OF FE ISOTOPES: EVIDENCE OF AN EQUILIBRIUM ISOTOPE EFFECT - Roe J.E.; Anbar A.D.; Barling J. (My University, 2003)
Fe isotopes can be fractionated to similar extent by both biological and nonbiological processes in the laboratory. However, fractionation mechanisms are not yet clear, making it difficult to generalize from the laboratory to natural systems. We have previously shown that Fe isotope fractionations of several per mil can be generated during anion exchange chromatography of Fe dissolved in HCl. Here, we present results of experiments designed to assess the importance of equilibrium Fe isotope effects in such systems. In batch equilibration rate experiments, including one using a 54Fe-enriched tracer to precisely determine the rate of exchange between dissolved and resin-bound Fe, equilibration was nearly complete within 1 min. In rate-dependent chromatographic elution experiments, the extent of isotope separation was found to increase significantly as flow rate decreased, demonstrating that the magnitude of Fe isotope fractionation increases as more time is allowed for equilibration. This observation provides very strong evidence of a significant equilibrium isotope effect, while also revealing that expression of this effect can be inhibited if the flow rate is higher than the time constant for equilibration. We propose that diffusion into resin pores is the rate-limiting step inhibiting complete expression of equilibrium isotope fractionation. Fractionation of Fe isotopes in this system most likely reflects an equilibrium effect during speciation between Fe chloro-aquo complexes, particularly between anionic, tetrahedral FeCl4- and the sixfold coordinated FeCl3(H2O)3# and FeCl2(H2O)4+. On theoretical grounds, such changes in bonding environment are likely to drive Fe isotope fractionation. The magnitude of the equilibrium fractionation factor is likely 1.0001 to 1.001. Extrapolating from these results, Fe isotope variations in nature cannot be uniquely ascribed to biology until nonbiological Fe isotope effects are better understood.
Keywords: FE; ISOTOPE COMPOSITION; MASS FRACTIONATION; ANION EXCHANGE CHROMATOGRAPHY